Penerapan Metode ARIMA untuk Meramalkan Harga Emas Terhadap Mata Uang Dolar Amerika Serikat - NA Mentacem; Arnellis Arnellis; Yenni Kurniawati (UNIVERSITAS NEGERI PADANG, 2019)
Abstract–Gold is one of precious metals group which has high value and often to be used as a investment object. Meanwhile, United States Dollar (USD) is the most stable currency among all of currencies in the world at this time. Gold and USD are the best investment object for keep our wealth from inflation. Based on these facts, it is necessary to forecast the price of gold in USD. The forecasting method that is used in this research is ARIMA method. The goal of this research is to get the prediction of gold price in USD in the future based on the price of gold from year 2009 to 2016 .The result of this research indicates that the ARIMA (1,1,1) model as the best model for forecasting. The complete equation is. Based on this model, the gold price in 2017 is going to increase. The prediction of gold’s price in January 2017 is USD 1,128 for every an ounce gold, and the price of gold in December is predicted will be at the point USD 1,171 for an ounce. Keywords–Gold Price, United States Dollar, ARIMA, Invesment